1998
DOI: 10.2739/kurumemedj.45.59
|View full text |Cite
|
Sign up to set email alerts
|

Chenges of Visual Performance Induced by Exposure to Whole-body Vibration.

Abstract: To clarify the effects of whole-body vibration (WBV) on visual performance, visual acuity and a self-rated assessment of difficulties in visible perception were determined after various frequencies of vibration in six healthy males. Two different sitting postures , an erect posture and a muscle-relaxed posture, were used. Sinusoidal vertical vibrations at ten frequencies (8, 10, 12.5, 16, 20, 25, 31.5, 40, 63.5 and 80 Hz) were applied to the seated subjects for 20 sec. The magnitude of acceleration at each vib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
17
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 6 publications
1
17
0
1
Order By: Relevance
“…All trials were performed on a commercial WBVE platform (Wave Pro Elite; WAVE TM ; Windsor, ON, Canada) that generated sinusoidal SV. Participants were exposed to vibration at selected frequencies of 20,25,30,35,40,45, and 50 Hz at nominal 1 and 2 mm p-p displacement settings. Each vibration exposure lasted 30-s, and a 120-s rest period was given between each experimental trial to minimize muscular fatigue.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…All trials were performed on a commercial WBVE platform (Wave Pro Elite; WAVE TM ; Windsor, ON, Canada) that generated sinusoidal SV. Participants were exposed to vibration at selected frequencies of 20,25,30,35,40,45, and 50 Hz at nominal 1 and 2 mm p-p displacement settings. Each vibration exposure lasted 30-s, and a 120-s rest period was given between each experimental trial to minimize muscular fatigue.…”
mentioning
confidence: 99%
“…The motion of the eyes during vibration is complex; being determined by the transmission of vibration to the head as well as between the head and the eye [ 17 ] . Resonance of the eye and retina is between 25 and 31.5 Hz [ 14 , 43 ] , while vibrations between 10 and 20 Hz cause major changes in visual acuity and self-rated assessment of vis- ual perception [ 20 ] . Based on our results it appears that there may be a greater risk of injury to the eyes and other structures of the head during WBVE with low frequencies ( < 30 Hz) combined with small KFAs due to the high magnitude of the transmissibility to the head.…”
mentioning
confidence: 99%
“…Short-term whole-body vibration exposure can affect visual performance depending on the vibration frequency and the sitting posture [19]. The visual acuity and self-rated assessment of visual disturbances may be influenced by the resonance frequency of the eyeball [19]. Low back pain is a common problem among the working adults as observed in this study particularly among rock drill workers (70%).…”
Section: Discussionmentioning
confidence: 70%
“…In the wholebody resonance frequency, there is a maximum displacement between the organs and the skeletal structure and thus, this is the vibration frequency that should be minimized in the workplace and elsewhere [18]. Short-term whole-body vibration exposure can affect visual performance depending on the vibration frequency and the sitting posture [19]. The visual acuity and self-rated assessment of visual disturbances may be influenced by the resonance frequency of the eyeball [19].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies report the influence of vibration on readability tasks but the effect on the performance of a data entry task has not been explored. Ishitake, Ando, Miyazaki, et al [27] found that the disturbances of visual performance were dependent on the vibration frequency with a maximum reduction of visual acuity at a frequency of 12.5 Hz. Griefahn, Bröde and Jaschinski [28] revealed that participants in the 19-26 years age range faced difficulty in properly recognizing characters and graphic patterns containing horizontal lines, and developed asthenopic complaints in the presence of 5-Hz sinusoidal single-and dual-axis (vertical and lateral) whole-body vibration.…”
Section: Discussionmentioning
confidence: 99%